Marcel Gautherot e a construção de Brasília: iconografia comentada - Viégas, Roberta Felippe (2012)
This paper has as its subject photographs produced by Marcel Gautherot during the building of Brasília. Through these images, an important historical, social, political and cultural moment of Brazil is rescued. The analysis of the photos leads us to different levels of research and to technical and aesthetic questions, which conducts the documental work of the photographer to another stage, approximating it to the arts. The aim of this research is to discuss the relation between photography and architecture, as well as the influence one may exercise on another, taking into consideration the role of the photography in which concerns to documentation, history and art; the images here displayed are actual cultural documents. In order to achieve this objective, besides the visual and critical reading of the images, a reflection about texts and theories related to the photographic universe has taken place. We have attempted to analyze how photographers assume the function of narrators, offering, therefore, a wide interpretation of the photographic subject